Motivational Interviewing for Health Sciences Students: The Results of Training - Souza, Fernanda Pasquoto de (2019)
This study sought to evaluate the effectiveness of Motivational Interviewing (MI) training on undergraduate students in the senior year of different healthcare courses. Using a pre and post-test quasi-experimental design, 60 undergraduate students received an eight-hour Motivational Interviewing basic skills training. Basic skills were assessed using a clinical vignette, the Confidence and Importance Ruler and The Helpful Responses Questionnaire, which was coded using the Motivational Interviewing Skill Code. The training was associated with improvements in motivational interviewing basic skills. Students also showed increased awareness of the importance of using these skills with patients, even after a brief training.